1997
DOI: 10.1002/jor.1100150304
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the flexibility characteristics of the ankle complex due to damage to the lateral collateral ligaments: An in vitro and in vivo study

Abstract: This study was part of a long-term effort to develop a reliable diagnostic procedure for ankle ligament injuries. Earlier efforts led to the development and validation of a six-degrees-of-freedom instrumented linkage capable of measuring the flexibility characteristics of the ankle complex in vitro and in vivo. The major goal of the present study was to determine if these flexibility measurements are sufficiently sensitive to detect the presence of damage to the lateral collateral ligaments of the ankle joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 54 publications
3
38
0
Order By: Relevance
“…We found variability in absolute values of inversion or internal rotation measured between patients. It is well recognised that there is wide variation among individuals in stress tests [6,12,13,23], which our testing confirmed. This observation in preliminary testing led to refinements in how the foot was secured to the footplate, standardising a neutral position prior to testing, and the repeatability study that was conducted.…”
Section: Discussionsupporting
confidence: 81%
“…We found variability in absolute values of inversion or internal rotation measured between patients. It is well recognised that there is wide variation among individuals in stress tests [6,12,13,23], which our testing confirmed. This observation in preliminary testing led to refinements in how the foot was secured to the footplate, standardising a neutral position prior to testing, and the repeatability study that was conducted.…”
Section: Discussionsupporting
confidence: 81%
“…10 The objective of testing after ankle-ligament sectioning was to assess and compare the passive mechanical stability characteristics of the ankle complex between the intact and ligament-deficient ankles. Numerous investigators 2,5,8,[10][11][12]15,18 have reported increased in vitro ankle-complex instability after isolated and sequential sectioning of the ATFL þ CFL when loaded in AP drawer and I-E. Fewer researchers 2,15,25 have reported the effects of ligament sectioning on stiffness characteristics of the ankle complex.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Increases in ankle-complex motion with isolated and combined sectioning of the ATFL and CFL have been reported extensively. 2,8,[10][11][12] General consensus in the literature is that measuring the relationship between ligament damage and joint laxity by simulating ligamentous injury in the cadaver specimen improves our understanding of joint motion and the effect ligament damage has on producing instability in the ankle-subtalar complex. Thus, objective documentation that describes change in the passive mechanical properties of the ankle complex with lateral ligament injury could be important in the differential diagnosis of these injuries.…”
mentioning
confidence: 99%
“…33 The potential of this device as an effective diagnostic tool for ankle ligament injuries has also been demonstrated by characterizing the changes produced in the load-displacement properties of the ankle resulting from ligament injuries. 18,19 Athletic tape with hyperelastic properties that are maintained after exercise and which decreases ankle/tape flexibility throughout a prolonged athletic activity may provide a significant improvement over the currently available conventional athletic tapes. The goal of this study was to introduce a hyperelastic tape and to compare its performance to that of conventional athletic tape.…”
Section: T T Conclusionmentioning
confidence: 99%
“…Such hyperelastic properties are exhibited naturally by biological structures, such as ligaments and tendons, 12,30,37 as well as by anatomical joints. 9,18 However, conventional athletic tapes or ankle braces do not possess such hyperelastic properties and substantially interfere with joint motion in its functional range, thus reducing comfort and athletic performance. 7,22,29 Furthermore, several previous studies have shown that conventional athletic tape loses its effectiveness (passive support) during exercise, with some studies reporting a reduction in support of up to 50% during the first 10 to 30 minutes.…”
mentioning
confidence: 99%